Factors influencing the cost-effectiveness of novel oral anticoagulants compared to vitamin K antagonists in patients with atrial fibrillation: a systematic review - Li, Yan; Wang, Xintian; Ma, Aixia; Chen, Pingyu; Li, Hongchao (Frontiers in Pharmacology, 2025)
BackgroundAtrial fibrillation (AF) is a common clinical arrhythmia, primarily associated with the risk of stroke and various thromboembolic events, imposing significant clinical and economic burdens on patients and societies. This study aimed to review the relevant pharmacoeconomic evaluations of novel oral anticoagulants (NOACs) compared to vitamin K antagonists (VKAs) in patients with AF and explore the influencing factors and general trends of economic evaluations.MethodsThis review qualitatively analyzed the basic characteristics, model structure, and basic results of all included studies. Moreover, a cross-sectional and longitudinal comparative analysis of costs, health outcomes, and cost-effectiveness results of studies in the United States, China, and the United Kingdom was conducted. Additionally, this study employed multivariate binary logistic regression to explore the influencing factors and general trends of the cost-effectiveness between NOACs and VKAs across all included studies.ResultsA total of 103 studies were included, comprising 218 comparisons between NOACs and VKAs. Total costs and health outcomes measured in studies with different countries and baseline characteristics exhibited considerable variations. However, NOACs generally had higher total costs than VKAs and resulted in more health outcomes for patients. The binary logistic regression analysis revealed that the country’s economic development level, study perspective, and cycle length significantly influenced cost-effectiveness results.ConclusionIn high-income countries, NOACs are generally considered cost-effective, while VKAs may remain an attractive strategy in middle- and low-income countries. Additionally, factors such as drug prices, patient baseline characteristics, and model settings could impact the costs, health outcomes, and cost-effectiveness results of studies. Conducting relevant pharmacoeconomic research based on specific populations and study contexts is essential.